Key Labor Market Indicators : Analysis with Household Survey Data - Pietschmann, Ina (Washington, DC: World Bank, 2016)
Key Labor Market Indicators: Analysis with Household Survey Data is an introduction to labor market indicator analysis and a guide for analyzing household survey data using the ADePT ILO (International Labour Organization) Labor Market Indicators Module. The analytical framework and approach taken up in this book are based on the ILO’s Key Indicators of the Labour Market (KILM). KILM indicators provide a strong basis on which to address key questions related to productive employment and decent work. The ADePT ILO Labor Market Indicators Module is a powerful tool for producing and analyzing KILM indicators using household survey data. The software allows researchers and practitioners to automate data production, to minimize data production errors, and to quickly produce a wide range of labor market data from labor force surveys or other household surveys that contain labor market information.